2010
DOI: 10.1007/s10787-010-0060-6
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of arthritis in rodents by a novel orally-available inhibitor of sphingosine kinase

Abstract: Our results suggest that ABC249640 is an orally available drug candidate with a good pre-clinical efficacy profile for the prevention and/or treatment of RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 31 publications
1
33
1
3
Order By: Relevance
“…The arthritic rats showed soft-tissue swelling around the ankle joints, during the acute period of arthritis, was considered to be due to oedema of periarticular tissues, such as ligaments and joint capsules. Several authors have reported that there is profound swelling in contralateral paw and similar pathological changes have also been observed in the present study (Fitzpatrick et al 2011;Schopf et al 2006). There was significant reduction in swelling of inflamed area in the rats treated with lupeol as well as indomethacin, indicating the anti-inflammatory property of lupeol.…”
Section: Discussionsupporting
confidence: 91%
“…The arthritic rats showed soft-tissue swelling around the ankle joints, during the acute period of arthritis, was considered to be due to oedema of periarticular tissues, such as ligaments and joint capsules. Several authors have reported that there is profound swelling in contralateral paw and similar pathological changes have also been observed in the present study (Fitzpatrick et al 2011;Schopf et al 2006). There was significant reduction in swelling of inflamed area in the rats treated with lupeol as well as indomethacin, indicating the anti-inflammatory property of lupeol.…”
Section: Discussionsupporting
confidence: 91%
“…However, the efficacy of SK inhibitors has not yet been tested in an animal model of OA. ABC294640 is a novel chemical compound that selectively inhibits SK2 and also improves experimental rheumatoid arthritis in rodents [17,18] . Therefore, we hypothesized that ABC294640 might also attenuate various features of MIA-induced OA, including apoptosis [10] .…”
mentioning
confidence: 99%
“…еже-дневно, с перерывом на выходные, проводили клиниче-ский осмотр животных с оценкой тяжести развития пато-логии в баллах. При отсутствии изменений инъецирован-ной лапы присваивалась оценка «0», при наличии слабо-выраженного отека -«1», при наличии отека и слабовы-раженного покраснения -«2», при наличии значительно-го отека и сильно выраженного покраснения -«3», при наличии сильно выраженного отека и покраснения, затрагивающих все суставы инъецированной лапы, и/или при генерализации процесса (вовлечение суставов контр латеральной лапы, суставов в основании хвоста, передних лап) -оценка «4» [28].…”
Section: потенцирование регенеративных процессов хряща и эффективностunclassified